Analysis of The Choreography of Kenes Ghandes Dance At Kinanti Sekar Art Studio - Rahina, Kinanti Sekar (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2023)
This study aims to read and recognize the 'Kenes Gandhes' dance work, a dance that depicts the agility and grace of Javanese women. It is developed from various dances found in several regions of the Special Region of Yogyakarta, choosing creative dance movements as its form. Kenes Gandhes dance, accompanied by vibrant music, is neatly packaged by its choreographer by combining elements and movements of Tradition and developing them into a new creative dance work. The choreographer and creator of Kenes Gandhes, Kinanti Sekar Rahina, categorizes Kenes Gandhes as a dance for children aged 13 to 21 years, after observing children at Kinanti Sekar Art Studio (SSKS) who show sufficient agility and energy in this age range. This dance can be performed by either a solo female dancer or a group, wearing yellow brocade costumes with short sleeves and batik skirts with the wahyu tumurun motif. This study uses a choreography approach proposed by Y. Sumandiyo Hadi, covering aspects of form, technique, and content, with basic elements consisting of movement, space, and time. The design of floor patterns, motion motifs, musical accompaniment, and choreography elements are structured into the choreographic form of Kenes Ghandes. This dance is expected to become one of the dance works that can develop in the general community to encourage ongoing love for culture. Additionally, this study seeks to explore the cultural values contained in the Kenes Gandhes dance to enrich the repertoire of dance art in Indonesia. This work is also expected to enhance public appreciation of local cultural richness and encourage the younger generation to preserve the nation's cultural heritage.